Amiloride Improves Endothelial Function and Reduces Vascular Stiffness in Female Mice Fed a Western Diet - Martinez-Lemus, Luis A.; Aroor, Annayya R.; Ramirez-Perez, Francisco I.; Jia, Guanghong; Habibi, Javad; DeMarco, Vincent G.; Barron, Brady; Whaley-Connell, Adam; Nistala, Ravi; Sowers, James R. (Frontiers in Physiology, 2017)
Obese premenopausal women lose their sex related cardiovascular disease protection and develop greater arterial stiffening than age matched men. In female mice, we have shown that consumption of a Western diet (WD), high in fat and refined sugars is associated with endothelial dysfunction and vascular stiffening, which occur via activation of mineralocorticoid receptors and associated increases in epithelial Na+ channel (ENaC) activity on endothelial cells (EnNaC). Herein our aim was to determine the effect that reducing EnNaC activity with a very-low-dose of amiloride would have on decreasing endothelial and arterial stiffness in young female mice consuming a WD. To this end, we fed female mice either a WD or control diet and treated them with or without a very-low-dose of the ENaC-inhibitor amiloride (1mg/kg/day) in the drinking water for 20 weeks beginning at four weeks of age. Mice consuming a WD were heavier and had greater percent body fat, proteinuria, and aortic stiffness as assessed by pulse-wave velocity than those fed control diet. Treatment with amiloride did not affect body weight, body composition, blood pressure, urinary sodium excretion or insulin sensitivity, but significantly reduced the development of endothelial and aortic stiffness, aortic fibrosis, aortic oxidative stress and mesenteric resistance artery EnNaC abundance and proteinuria in WD-fed mice. Amiloride also improved endothelial-dependent vasodilatory responses in the resistance arteries of WD-fed mice. These results indicate that a very-low-dose of amiloride not affecting blood pressure is sufficient to improve endothelial function and reduce aortic stiffness in female mice fed a WD, and suggest that EnNaC-inhibition may be sufficient to ameliorate the pathological vascular stiffening effects of WD-induced obesity in females.